Workplace Bullying :Shape up or Ship Out - Rather, Bilal Ahmad (International Journal of Management Excellence (ISSN: 2292-1648), 2016)
In these times of global unemployment crises, a job is not just a means of survival but a way of living with dignity and honour. However, things turnaround for significant percentage of working population all over the globe and they don’t find in work what they originally joined it for. The workplace gets hostile to them, people behave aggressively, they feel harassment …. They get bullied. In this study we try to show how big a menace the workplace bullying is. We focus on its devastating effects on the lives of people and the organizational culture. By taking suitable examples from various researches, books, magazines, essays, government reports, NGOs and other highly accepted online sources, we try to show how lethal it could be for an organization if it gives in to the disease of workplace bullying. The study suggests some measures about how management can exercise control and ensure the work environment becomes appealing and result in the better productivity and profitability. Our study is driven by the belief that bullying of every kind needs to be stopped at every level and employees be given the relaxed and dignified workplace to work at. This reading should serve as a motivational tool for the organizations where bullying of any sort is prevalent, to check , control and make sure the employees are taking pride in being part of their work culture. Further, the reader shall gain the significant understanding of people involved in this act and effects it may have on the lives of victims and organizational efficiency.